The effect of ZrO2 buffer layer on electrical properties in Pt/SrBi2Ta2O9/ZrO2/Si ferroelectric gate oxide structure - Choi, HS; Kim, EH; Choi, IH; Kim, YT; Choi, JH; Lee, JY (ELSEVIER SCIENCE SA, 2001)
We have investigated metal/ferroelectric/insulator/semiconductor (MFIS) structure with strontium bismuth tantalate (SBT) as ferroelectric thin film and ZrO2 as the insulating buffer layer. Sr0.8Bi2.4Ta2O9 thin films were prepared by metal organic deposition (MOD) method and ZrO2 films were deposited by r.f.-sputtering. Coercive field that decisively affects the memory window was increased greatly by inserting the ZrO2 insulator between SET and SiO2 and, thus, the memory window also increases with an electric field to the SET. Memory windows of MFIS structure were in the range of 0.3-2.6 V when the gate voltage varied from 3 to 10 V. Memory windows of MFIS structure were found to be dependent on the thickness of the buffer layer. We observed the maximum memory window in MFIS with a 28-nm thickness of ZrO2 layer. Auger electron spectroscopy (AES) depth profile and high resolution transmission electron microscopy (HRTEM) of SBT/ZrO2 (28 nm)/Si structure showed that the ZrO2 thin films as a buffer layer helped to prevent the formation of interfacial layer and interdiffusion between SET and Si. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: THIN-FILMS; MEMORIES